2021
DOI: 10.1016/j.dcn.2021.100952
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for dissociable cognitive and neural pathways from poverty versus maltreatment to deficits in emotion regulation

Abstract: Poverty and threat exposure (TE) predict deficits in emotion regulation (ER). Effective cognitive ER (i.e., reappraisal) may be supported by: (1) cognitive processes implicated in generating and implementing cognitive reappraisal, supported by activation in brain regions involved in cognitive control (e.g., frontal, insular, and parietal cortices) and (2) emotion processing and reactivity, involving identification, encoding, and maintenance of emotional states and related variation in brain activity of regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 72 publications
1
0
0
Order By: Relevance
“…Follow-up analyses found that even within the group of children in poverty, the direction of the relation seemed to differ meaningfully for children below poverty with different sets of experiences, such as parent-reported neighborhood safety and the type of school children attended. These follow-up analyses are in keeping with other work showing that different socioeconomic indicators and early experiences are differentially related to neural development (e.g., Elsayed et al, 2021; Johnson et al, 2016; Noble et al, 2015; Rakesh, Zalesky, et al, 2021; Taylor et al, 2020; Whittle et al, 2017). Our unexpected results suggest that in certain environments it may be adaptive to frequently coactivate LFPN and DMN (Ellwood-Lowe et al, 2020).…”
Section: Introductionsupporting
confidence: 88%
“…Follow-up analyses found that even within the group of children in poverty, the direction of the relation seemed to differ meaningfully for children below poverty with different sets of experiences, such as parent-reported neighborhood safety and the type of school children attended. These follow-up analyses are in keeping with other work showing that different socioeconomic indicators and early experiences are differentially related to neural development (e.g., Elsayed et al, 2021; Johnson et al, 2016; Noble et al, 2015; Rakesh, Zalesky, et al, 2021; Taylor et al, 2020; Whittle et al, 2017). Our unexpected results suggest that in certain environments it may be adaptive to frequently coactivate LFPN and DMN (Ellwood-Lowe et al, 2020).…”
Section: Introductionsupporting
confidence: 88%